Appearance of efficient luminescence energy transfer in doped orthovanadate nanocrystals. Issue 3 (27th April 2017) - Bishnoi, Swati; Swati, G.; Singh, Paramjeet; Jaiswal, V. V.; Sahu, Mukesh K.; Gupta, Vinay; Vijayan, N.; Haranath, D.
Abstract : Efficient luminescence energy transfer in doped orthovanadate nanocrystals is reported. Abstract : This paper reports the detailed synthesis mechanism and the structural, morphological and optical characterization of ultraviolet (∼311 nm) excitable samarium doped gadolinium yttrium orthovanadate, (Gd, Y)VO4 :Sm 3+, nanocrystals. X‐ray diffraction and Rietveld refinement studies confirmed that the synthesized samples crystallize in a tetragonal structure with I 41/ amd space group. The enhanced photoluminescence intensity of (Gd, Y)VO4 :Sm 3+ compared with the existing YVO4 :Sm 3+ phosphor clearly indicates the significant role of Gd 3+ ions. This has been attributed to the sensitization of the 6 P J energy level of Gd 3+ ions by energy transfer from orthovanadate (VO4 3− ) ions and subsequent energy trapping by Sm 3+ ions. The energy transfer from VO4 3− to Sm 3+ via Gd 3+ ions as intermediates and concentration quenching of Gd 3+ luminescence are discussed in detail. The optical band gap of the as‐prepared nanocrystals has been estimated using UV–vis–NIR absorption spectroscopy, which reveals a slightly higher band gap (3.75 eV) for YVO4 as compared to GdYVO4 (3.50 eV). Furthermore, confocal microcopy, decay parameters and Commission Internationale de l'Eclairage chromatic coordinates have supplemented these studies, which established the suitability of these nanophosphors for achieving spectral conversion in silicon solar cells.